Primary central nervous system tumors in Sergipe, Brazil: descriptive epidemiology between 2010 and 2018 - SANTOS, Bárbara Loiola; OLIVEIRA, Arthur Maynart Pereira; OLIVEIRA, Hélio Araújo; AMORIM, Robson Luis Oliveira de (Arquivos de Neuro-Psiquiatria, 2021)
Background: Central nervous system (CNS) tumors are a heterogeneous group with high morbidity and mortality. Objectives: To describe the epidemiology of primary CNS tumors diagnosed in the state of Sergipe from 2010 to 2018. Methods: We evaluated histopathological and immunohistochemical reports on primary CNS tumors diagnosed in Sergipe, Brazil, between 2010 and 2018 and collected data regarding age, sex, location, World Health Organization (WHO) classification and histology. Results: Altogether, 861 primary CNS tumors were found. Tumors in brain locations occurred most frequently (50.8%; n=437). The neoplasms observed were most prevalent in the age range 45–54 years (20.4%; n=176). Grade I tumors occurred most frequently, corresponding to 38.8% of the cases (n=38) in the age group of 0–14 years, and 44.6% (n=340) in the population ≥15 years old. Between 0 and 14 years of age, other astrocytic tumors were the most prevalent (29.6%; n=29). In the age group between 15 and 34, gliomas were the most frequent (32.7%; n=54). Meningiomas predominated in the age group of 35 years and above, comprising 47.5% of cases (n=206) in the 35–74 age group; and 61.2% (n=30) among patients over 75 years old. Conclusion: The epidemiology of primary CNS tumors in Sergipe between 2010 and 2018 is consistent with data in other current studies on the subject. Studies on the epidemiological evolution of these entities in Sergipe are needed.
Keywords: Brain Neoplasms; Epidemiology; Prevalence